Nanocrystalline W-based alloys with ultrahigh hardness and exceptional irradiation tolerance. (9th September 2019) - Wu, Z.M.; Zhang, J.; Zhang, J.; Huang, J.C.; Fan, Y.; Yu, X.H.; Zhao, Y.B.; Zhu, J.L.; Jin, C.Q.; Wang, P.; Fu, E.G.
Abstract: Nanocrystalline W-5 wt.% Y2 O3 (WYO) with an average grain size of 10 nm and W-5 wt.% Y2 O3 -2.5 wt.% Ni (WYON) with an average grain size of 85 nm were successfully fabricated for the first time using a high-energy ball-milling method followed by a resistance sintering under ultrahigh pressure (RSUHP) technique. Investigation of the microstructure of sintered WYO shows that the intergranular doping of Y2 O3 grains inhibits the grain growth of W, and investigation of the microstructure of sintered WYON shows that the addition of Ni atoms leads to the grain growth and density increase. The Vickers hardness of sintered WYO and sintered WYON is much higher than that of ITER grade W. The He bubble areal density and swelling of WYO and WYON are much lower than those of ITER grade W, indicating that WYO and WYON possess exceptional higher irradiation tolerance in terms of He ion damage than coarse-grained ITER grade W. This study demonstrates the promising applications of nanocrystallined W-based alloys as plasma-facing materials (PFMs) due to their ultrahigh hardness and excellent radiation tolerance.